Consulting report – DSB Mobile - Mitta, Ever (Pontificia Universidad Católica del Perú, 2017)
DSB Mobile is a small Peruvian software developing company based in Lima. DSB Mobile specializes in the development of both mobile and web applications and has worked with major companies such as Samsung, Claro & Entel. The company is composed of the General Manager, Zico Herrera, a sales manager, operations manager and both fulltime and contract based software developers that are hired based on the current demand for service. DSB Mobile has established a strong reputation and brand in Peru and is now looking to expand outside of Peru where they can introduce their software products into international markets. In their aspiration to internationalize, DSB Mobile is seeking to find out not only the most profitable markets for their company but also markets that would best align with DSB Mobiles mission. The solution to their question of expansion was to determine the best markets using a variety of both quantitative and qualitative factors. In using an IT Competitiveness report that was done by the British Software Alliance this was used as a reference point to determine the best ranked countries for IT competitiveness and the best countries to conduct business in base off of important IT indicators. Combined with software data statistics in terms of charges per project and cost of IT Consultants, this further narrowed down the scope to the most attractive, profitable and mutually beneficial market for DSB Mobile. The implementation plan proposed involved two market lines namely, the North American market line and the European Market line. The proposed solution takes into consideration different scenarios, one of them being the moderate work balance of 1 project per month, giving a total cost of $391,065 per year with a profit of $180,736. The Gantt chart outlined is intended to guide the company with the step by step implementation of this international expansion and prepare them to execute this plan in the most efficient and effective manner

DSB Mobile es una pequeña empresa peruana de desarrollo de software con sede en Lima. DSB Mobile se especializa en el desarrollo de aplicaciones móviles y web y ha trabajado con grandes empresas como Samsung, Claro y Entel. La compañía está compuesta por el Gerente General, Zico Herrera, un gerente de ventas, un gerente de operaciones y desarrolladores de software a tiempo completo y algunos que se contratan en base a la demanda actual de servicio. DSB Mobile ha establecido una fuerte reputación y marca en Perú y ahora está buscando expandirse fuera de Perú donde puedan introducir sus productos de software en los mercados internacionales. En su aspiración de internacionalización, DSB Mobile está tratando de descubrir no sólo los mercados más rentables para su empresa, sino también los mercados que mejor se alinean con la misión DSB Mobile. La solución a su problema de expansión fue determinar los mejores mercados utilizando una variedad de factores tanto cuantitativos como cualitativos. Al utilizar un informe de competitividad de TI que fue realizado por la British Software Alliance, se utilizó como punto de referencia para determinar los países mejor clasificados para la competitividad de TI y los mejores países para llevar a cabo negocios en base de importantes indicadores asociados a estos. Combinado con estadísticas de datos de software en términos de gastos por proyecto y coste de consultores en TI, esto permitió reducir aún más el alcance para obtener un mercado más atractivo, rentable y mutuamente beneficioso. El plan de implementación propuesto involucró dos líneas de mercado, a saber, la línea del mercado norteamericano y la línea del mercado europeo. La solución propuesta posee diferentes escenarios; por ejemplo, el escenario con trabajo moderado consta de 1 proyecto por mes y tiene un costo total de $391,065 por año obteniendo así una rentabilidad de $180,736. El gráfico de Gantt esbozado pretende guiar a la compañía con la implementación paso a paso de esta expansión internacional y prepararlos para ejecutar este plan de la manera más eficiente y efectiva
Keywords: Empresas -- Crecimiento económico -- Perú; Empresas -- Organización; https://purl.org/pe-repo/ocde/ford#5.02.04